The glorious adventures of Tyl Ulenspiegel - De Coster, Charles; Huysmans, Camille; Masereel, Frans (New York : Pantheon Books, 1943)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Tijl Uilenspiegel; legenden; folklore